Studies on drying characteristics and effect of pretreatment on the quality of sun-dried oyster mushroom, Pleurotus florida - Arumuganathan, T; Kumar, Anil; K, Hemkar; Rai, R D (Mushroom Research, 2015)
Please see the full text